PERBEDAAN HASIL BELAJAR MATEMATIKA SISWA SMP N 1 RAMBAH HILIR ANTARA YANG MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENTS TEAMS ACHIEVEMENT DIVISIONS (STAD) DAN NUMBERED HEAD TOGETHER (NHT) - Yulianti, Iin; -, Arcat; -, Suwandi (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2015)
This research aims to determine the differences in students mathematic learning outcomes SMP N 1 Rambah Hilir between the use of cooperative learning model Student Teams Achievement Divisions (STAD) and Numbered Head Together (NHT). In this study the formulation of the problem is "Is there concluded that was found difference of the result students mathematics learning SMP N 1 Rambah hilir between the use of cooperative learning model Student Teams Achievement Divisions (STAD) and Numbered Head Together (NHT)? The object of this study is the result of learning students mathematic. Researchers used the test "tâ" to analyze the data. From the analysis of data it can be concluded that there was difference of the result students mathematics learning SMP N 1 Rambah hilir between the use of cooperative learning model Student Teams Achievement Divisions (STAD) and Numbered Head Together (NHT).